Granular and particle-laden flows: from laboratory experiments to field observations. (5th January 2017) - Delannay, R; Valance, A; Mangeney, A; Roche, O; Richard, P
Abstract: This review article provides an overview of dry granular flows and particle fluid mixtures, including experimental and numerical modeling at the laboratory scale, large scale hydrodynamics approaches and field observations. Over the past ten years, the theoretical and numerical approaches have made such significant progress that they are capable of providing qualitative and quantitative estimates of particle concentration and particle velocity profiles in steady and fully developed particulate flows. The next step which is currently developed is the extension of these approaches to unsteady and inhomogeneous flow configurations relevant to most of geophysical flows. We also emphasize that the up-scaling from laboratory experiments to large scale geophysical flows still poses some theoretical physical challenges. For example, the reduction of the dissipation that is responsible for the unexpected long run-out of large scale granular avalanches is not observed at the laboratory scale and its physical origin is still a matter of debate. However, we believe that the theoretical approaches have reached a mature state and that it is now reasonable to tackle complex particulate flows that incorporate more and more degrees of complexity of natural flows.